Topological Distribution of Wound Stiffness Modulates Wound-Induced Hair Follicle Neogenesis - Hans I-Chen Harn; Po-Yuan Chiu; Chein-Hong Lin; Hung-Yang Chen; Yung-Chih Lai; Fu-Shiuan Yang; Chia-Ching Wu; Ming-Jer Tang; Cheng-Ming Chuong; Michael W. Hughes (MDPI AG, 2022)
In the large full-thickness mouse skin regeneration model, wound-induced hair neogenesis (WIHN) occurs in the wound center. This implies a spatial regulation of hair regeneration. The role of mechanotransduction during tissue regeneration is poorly understood. Here, we created wounds with equal area but different shapes to understand if perturbing mechanical forces change the area and quantity of de novo hair regeneration. Atomic force microscopy of wound stiffness demonstrated a stiffness gradient across the wound with the wound center softer than the margin. Reducing mechanotransduction signals using FAK or myosin II inhibitors significantly increased WIHN and, conversely, enhancing these signals with an actin stabilizer reduced WIHN. Here, α-SMA was downregulated in FAK inhibitor-treated wounds and lowered wound stiffness. Wound center epithelial cells exhibited a spherical morphology relative to wound margin cells. Differential gene expression analysis of FAK inhibitor-treated wound RNAseq data showed that cytoskeleton-, integrin-, and matrix-associated genes were downregulated, while hair follicular neogenesis, cell proliferation, and cell signaling genes were upregulated. Immunohistochemistry staining showed that FAK inhibition increased pSTAT3 nuclear staining in the regenerative wound center, implying enhanced signaling for hair follicular neogenesis. These findings suggest that controlling wound stiffness modulates tissue regeneration encompassing epithelial competence, tissue patterning, and regeneration during wound healing.